2016
DOI: 10.1002/jhet.2609
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Pseudo Five‐Component Synthesis of Some New bis(Quinazolinon‐4(1H)‐one) Derivatives

Abstract: A versatile pathway for the synthesis of novel bis(quinazolinon‐4(1H)‐one) derivatives by one‐pot pseudo five‐component condensation of two molecules isatoic anhydrides, two molecules orthoesters, and diamines in high yields and short reaction time is described. The work‐up is easy, and the products are obtained in good‐to‐excellent yields and high purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Two intramolecular nucleophilic additions of 82 lead to the formation of products 81 . The same group applied this method for the synthesis of bis(quinazolinon-4(1 H )-one) derivatives 83 by replacing isatins with orthoesters ( Scheme 34 ) [ 49 ].…”
Section: Type-iii Pseudo-5crs Of 2a + 2b + Cmentioning
confidence: 99%
“…Two intramolecular nucleophilic additions of 82 lead to the formation of products 81 . The same group applied this method for the synthesis of bis(quinazolinon-4(1 H )-one) derivatives 83 by replacing isatins with orthoesters ( Scheme 34 ) [ 49 ].…”
Section: Type-iii Pseudo-5crs Of 2a + 2b + Cmentioning
confidence: 99%
“…Bis(quinazolinon-4(1H)-one) derivatives (622) were also synthesized via the regioselective one-pot pseudo vecomponent cyclocondensation reaction of isatoic anhydride (312), orthoesters (5,6,7,102,323,455), and diamines (621) using KAl(SO 4 ) 2 $12H 2 O (alum, 20 mol%) as an inexpensive, ecofriendly, readily available, easily separable, and recyclable catalyst in reuxing DMF within 30-50 min in good to excellent yields (79-90%) (Scheme 188). 498 4-Arylaminoquinazolines 499 were synthesized in excellent yields (84-96%) within 2 h via the one-pot three-component condensation reaction of 2-aminobenzamide, anilines, and orthoesters by a catalytic amount of Keggin-type heteropolyacid (H 6 [PMo 9 V 3 O 40 ], 0.03 mmol) in reuxing CH 3 CN. Signicantly, anilines containing electrondonating groups were obtained in slightly better yield.…”
Section: Synthesis Of Quinazoline Derivativesmentioning
confidence: 99%
“…Phenylhydrazines can replace amines on treatment with isatoic anhydrides and orthoesters, generating 2‐alkyl and/ or 2‐aryl‐3‐(phenylamino)quinazolin‐4(3 H )‐ones in the presence of KAl(SO 4 ) 2 .12H 2 O (alum) in a one‐pot process. It was also shown that the reactions of isatoic anhydrides and orthoesters with ethylenediamines or phenylenediamines in refluxing DMF and in the presence of alum produce 3,3’‐di‐(2‐substituted‐4(3 H )‐quinazolinonyl)ethanes or 3,3’‐di‐(2‐substituted‐4(3 H )‐quinazolinonyl)benzenes respectively, depending on the applied diamine (Scheme ).…”
Section: Carbon‐carbon and Carbon‐heteroatom Bond Formation Reactionsmentioning
confidence: 99%
“… Synthesis of 3,3’‐di‐(2‐substituted‐4(3 H )‐quinazolinonyl)ethanes and 3,3’‐di‐(2‐substituted‐4(3 H )‐quinazolinonyl)benzenes …”
Section: Carbon‐carbon and Carbon‐heteroatom Bond Formation Reactionsmentioning
confidence: 99%